Children’s fitness, physical activity and motor competency; before, during and in the recovery from the COVID-19 pandemic - AMIE RICHARDS (2024)
Children do not engage in sufficient amounts physical activity, to promote fitness and motor competence, which is essential for children’s health, growth, and development. More evidence is required on physical activity levels, associations between motor competencies and fitness, and perhaps most importantly, the potential long-term effects of the COVID-19 pandemic. The overarching aim of this research was to investigate children’s physical activity, fitness, and motor competence. Given the COVID-19 pandemic and unprecedented impact that had on individual behaviours whilst this project was ongoing, this research also investigated the impact of this onphysical activity levels in children before, during and in the recovery from the pandemic.Study one synthesised pre-pandemic data to produce the Active Healthy Kids Wales 2021 Report Card. The results highlighted that 8/11 grades remained the same or decreased between 2016 and 2018. For deeper insight the second investigation found that physical fitness was associated with swimming and cycling competencies after accounting for age, body mass index, deprivation, gender, and sports club attendance and our third study, revealed a significant inequality in motor competence between children with and without additional learning needs.The natural experiment that occurred through COVID-19 allowed for the fourth piece of empirical work to use a qualitative approach to explore parents and children’s perceptions of children’s physical activity and sedentary behaviours within the home during the first lockdown of the COVID-19 pandemic. Results revealed a decrease in the children’s physical activity and an increase in sedentary behaviour; with barriers to physical activity including home-schooling and access to media equipment and facilitators including siblings and outside space. As an extension to study 4, the final study explored changes in children’s physical activity and sedentary behaviour at three time points throughout the pandemic. Reductions in children’s autonomy and relatedness during the lockdown restrictions led to decreases in physical activity and increases in sedentary time, some of which remained low when restrictions were eased.This novel body of research reiterates children’s low levels of physical activity while noting the importance of swimming and cycling competencies for fitness. Moreover, children’s activity remains below pre-COVID levels and public health messages for parents and teachers are imperative for children’s healthy development and wellbeing. There remains a need for additional nationwide mixed-methodology research into these levels and attributes of children’s physical activity.